2020
DOI: 10.1634/theoncologist.2019-0951
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Outcomes of Nonmetastatic Breast Cancer in Haiti: Results from a Retrospective Cohort

Abstract: Background There are few studies on breast cancer outcomes in the Caribbean region. This study identified a retrospective cohort of female patients with nonmetastatic breast cancer in Haiti and conducted survival analyses to identify prognostic factors that may affect patient outcomes. Methods The cohort included 341 patients presenting between June 2012 and December 2016. The primary endpoint was event‐free survival (EFS), defined as time to disease progression, recurrence, or death. Descriptive summaries of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…DeGennaro et al [ 32 ] reported invasive ductal carcinoma in 87.3% of women, with a prevalence of 51.8% ER+ tumors (supposed overestimation due to over fixation), 19.6% HER2+ tumors, and 38.5% TNBC. The prevalence of 83.9% by late-stage diagnosis mentioned earlier (Patient Demographics) corresponds to Fadelu et al [ 33 ] whose cohort had 53.4% late-stage tumors (given that 23.5% were of an unknown stage). In addition, George et al [ 71 ] found the highest percentage of advanced-stage disease in Haiti in comparison to other Caribbean countries studied, where 64.7% (44 of 68) had stage III/IV BC.…”
Section: Reviewsupporting
confidence: 65%
See 3 more Smart Citations
“…DeGennaro et al [ 32 ] reported invasive ductal carcinoma in 87.3% of women, with a prevalence of 51.8% ER+ tumors (supposed overestimation due to over fixation), 19.6% HER2+ tumors, and 38.5% TNBC. The prevalence of 83.9% by late-stage diagnosis mentioned earlier (Patient Demographics) corresponds to Fadelu et al [ 33 ] whose cohort had 53.4% late-stage tumors (given that 23.5% were of an unknown stage). In addition, George et al [ 71 ] found the highest percentage of advanced-stage disease in Haiti in comparison to other Caribbean countries studied, where 64.7% (44 of 68) had stage III/IV BC.…”
Section: Reviewsupporting
confidence: 65%
“…In Haiti, BC presents at an earlier age and at an advanced stage, predicted anecdotally by DeGennaro et al [ 32 ], and supported by their findings where more than half (53.8%) of the BC cases were in women aged 40-59 years at diagnosis (median 49 years), 49.2% premenopausal women, and 83.9% of cases diagnosed at stage III/IV. Fadelu et al [ 33 ] also observed a median age of diagnosis at 49 years with 64.2% being premenopausal, as with Gomez et al [ 57 ], where the median age at presentation was 48.5 years among their Haitian cohort in contrast to a median of 54 years in their Miami immigrant cohort. DeGennaro et al, (2018) [ 32 ] contend the unavailability of Haitian population data to be able to calculate age-adjusted rates for significant analysis.…”
Section: Reviewmentioning
confidence: 81%
See 2 more Smart Citations
“…This study extends existing knowledge about breast cancer in low‐ and lower‐middle‐income countries by specifically characterizing disease characteristics, patterns of care and treatment adherence in a center with access to radiotherapy. Parallel to previously published series in the region, most women presented with locally advanced or metastatic disease 3,28‐32 . Also like most countries in the region, Zimbabwe does not currently have a national breast cancer screening program.…”
Section: Discussionmentioning
confidence: 71%